2015
DOI: 10.1161/circulationaha.114.012826
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Perceived Stress and Early Recovery in Young and Middle-Aged Patients With Acute Myocardial Infarction

Abstract: Background Younger age and female sex are both associated with greater mental stress in the general population, but limited data exist on status of perceived stress in young and middle-aged patients presenting with acute myocardial infarction (AMI). Methods and Results We examined sex difference in stress, contributing factors to such difference, and whether this difference helps explain sex-based disparities in 1-month recovery using data from 3,572 AMI patients (2,397 women and 1,175 men) 18–55 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 33 publications
10
82
1
5
Order By: Relevance
“…Xu et al showed that among patients with acute MI, women were working less frequently and presented with higher psychological stress than men 19. Similarly, in our analysis, more women than men were living alone, were not working, and had more perceived psychological stress and depressive symptoms.…”
Section: Discussionsupporting
confidence: 73%
“…Xu et al showed that among patients with acute MI, women were working less frequently and presented with higher psychological stress than men 19. Similarly, in our analysis, more women than men were living alone, were not working, and had more perceived psychological stress and depressive symptoms.…”
Section: Discussionsupporting
confidence: 73%
“…The Framingham Heart Study reported a higher risk of cardiovascular disease in postmenopausal women that was even more pronounced in women aged 40 to 44 years,37 whereas the Nurses’ Health Study found no significant association with time since natural menopause 38. Socioeconomic status and level of depression may also play an important role in ACS prognosis in women 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…Sexo feminino foi, juntamente com outras variáveis independentes, preditor de maiores níveis de estresse percebido, o que corroborou com o encontrado na literatura (37).…”
Section: Discussionunclassified